Analisa Identitas Visual Karya Firma Desain Chermayeff & Geismar & Haviv - Putra, Hengky Dwi; Ria Sapitri; Supandi, Fajar Persada (Puslitabmas Batam Tourism Polytecnic, 2024)
Chermayeff & Geismar & Haviv is a brand design firm in New York City, United States specialising in visual identities. Since established in 1957, the firm has succeeded in creating the most recognisable visual identities and logos such as Mobil, NBC Television, Warner Bros Discovery, Open US, and many more. Their memorable logo works have earned the firm a good reputation on a global scale. Therefore, this research aims to analyse the quality of the firm’s work through portfolio observation techniques using semiotics theory. The results showed that the success of the firm's visual identity works departed from simplicity, and the simplicity of logo designs in this technological era has slowly begun to fade. With this research, it is hoped that readers, especially visual identity designers, can gain insight into how to create distinctive and memorable visual identity works through simplicity.